THE ERROR ANALYSIS OF REGULAR AND IRREGULAR VERBS IN THE SIMPLE PAST TENSE - Mukhlasul Fasikh (Journal of English Language and Literature (JELL), 2020)
This study aims to identify how many average students who are able to understand the use of regular and irregular verbs and to find out how many percentages of errors in using regular and irregular verbs and also to find out the source of error in using regular and irregular verb and also to make teaching and learning activities more effective and efficient. This research is descriptive research method. The Writer uses the questioners to collect the data. Students answer the questions and choose the best respond to complete the affirmative, negative, and interrogative sentences. The writer finds out the average of students who are able to understand the use of regular and irregular verbs by answering questions correctly is 11.8. The total percentage of errors in using regular and irregular verbs is 70.48% and 29.52% of students are able to answer correctly. The source of errors that many students have made is from overgeneralization and both transfer of knowledge which is interlingual and intralingual transfer.